The manifold uses of –a in Naro, including comments on a. - Hessel Visser (Studies in African Linguistics, 2023)
Several homophones –a occur in Naro. In this paper, an attempt is made to disambiguate the functional properties of –a, and also of the stand-alone a. The different uses will be shown, together with examples of each. A distinction is made between uses of–a carrying syntactic meaning, and occurrences where no syntactic meaning of –a can be identified. Differences between the –a suffixes and the a words are shown, followed by some statistical information, plus a transcribed Naro text to show the environments in which these morphemes occur.